AIR BUBBLE FORMATION PROCESS OBSERVED IN THE G6 ANTARCTIC ICE CORE - ミタニ, アタウ; ショウジ, ヒトシ; フジイ, ヨシユキ; MITANI, Atau; SHOJI, Hitoshi; FUJII, Yoshiyuki (National Institute of Polar Research, 1992)
P(論文) Air bubble formation processes were investigated on a 100m-long ice core from G6,Antarctica (73°07'S, 39°46'E). The observational results revealed clearly the five-stage process of air bubble entrapment. The pore space was closed off at a depth of 72m, which leads to about 470 years age difference between air bubbles and the ice estimated under an assumption of 9cm of ice/year for the accumulation rate. departmental bulletin paper